PARP inhibition-associated heterochromatin confers increased DNA replication stress and vulnerability to ATR inhibition in SMARCA4-deficient cells - Kimiyoshi Yano; Megumi Kato; Syoju Endo; Taichi Igarashi; Ryoga Wada; Takashi Kohno; Astrid Zimmermann; Heike Dahmen; Frank T. Zenke; Bunsyo Shiotani (Cell Death Discovery)
Abstract DNA replication stress (RS), a prevalent feature of various malignancies, arises from both genetic mutations and genotoxic exposure. Elevated RS levels increase the vulnerability of cancer cells to ataxia telangiectasia and Rad3-related kinase inhibitors (ATRis). Here, we screened for DNA damage response inhibitors that enhance ATRi-induced cytotoxicity using SWI/SNF complex-deficient cells and identified a potent synergy between ATRi and poly(ADP-ribose) polymerase inhibitor (PARPi), particularly in SMARCA4-deficient cells. PARP inhibition triggers chromatin changes, namely elevated histone H3 at lysine 9 di-methylation (H3K9me2), a hallmark of facultative heterochromatin, increasing dependence on ATR activity for replication fork progression and cell survival. Interestingly, SMARCA4 deficient cells, intrinsically vulnerable to replication stress, exhibited exacerbated DNA damage upon combined ATRi and PARPi treatment in a Mre11- and Mus81-mediated manner. In vivo, combined treatment with intermittent ATRi and continuous PARPi showed greater inhibition of tumor growth than ATRi alone in SMARCA4-deficient lung adenocarcinoma xenograft models. These findings demonstrate that PARPi-induced heterochromatin amplifies RS and ATRi susceptibility, providing a potential rationale for therapeutic strategies targeting SMARCA4-deficient tumors.